Lupeol alters viability of SK-RC-45 (Renal cell carcinoma cell line) by modulating its mitochondrial dynamics. Issue 8 (August 2019) - Sinha, Krishnendu; Chowdhury, Sayantani; Banerjee, Sharmistha; Mandal, Bhagirath; Mandal, Mullicka; Majhi, Sasadhar; Brahmachari, Goutam; Ghosh, Jyotirmoy; Sil, Parames C.
Abstract: Renal cell carcinoma (RCC) is the most common kidney cancer leading to 140, 000 deaths per year. Among all RCCs 80% evolve from the epithelial proximal tubular cells within the kidney. There is a high tendency of developing chemoresistance and resistance to radiation therapy in most RCC patients. Therefore, kidney resection is considered as the most effective treatments for patients having localized RCC. There is a high tendency of post-operative recurrence among 20–40% of the patients and this recurrence is not curable. It is also clear that modern medicine has no curative treatment options against metastatic RCC. Lupeol [lup-20(29)-en-3β-ol] is a pentacyclic triterpenoid compound naturally found in various edible fruits and in many traditionally used medicinal plants, and has been demonstrated as effective against highly metastatic melanoma and prostate cancers. The present study was designed to evaluate the effect of lupeol to RCC with molecular details. Treatment with lupeol on SK-RC-45 (a RCC cell line) with the LC50 dose of 40μM (for 48 h) induces mitochondrial hyper fission which eventually leads to apoptosis while SK-RC-45 counteracts by enhancing autophagy-mediated selective removal of fragmented mitochondria. This is the first study which concurrently reports the effects of lupeol on RCC and its effect on the mitochondrial dynamics of a cell. Herein, we conclude that lupeol has potential to be an effective agent against RCC with the modulation of mitochondrial dynamics.